The Effect of Murottal Al-Quran on the Level of Anxiety in Breast Cancer Patients Undergoing Chemotherapy at Ibnu Sina Hospital Makassar - Arliana Arlin; Faisal Sommeng; Sigit Dwi Pramono; Reeny Purnamasari; Febie Irsandy Syahrudin (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Anxiety is a serious problem in cancer patient’s sufferers, especially breast cancer undergoing chemotherapy. It has an impact on reducing the quality of life and the success of treatment. A breast cancer sufferer start to experience psychological disorders from the diagnosis is established, undergoing treatment, during and after treatment, both surgery and chemotherapy. Anxiety is generally develop base on fearness about bad future, such as losing family support or even death. Listening to murrotal chanting will stimulate the brain to release Gamma Amino Butyric Acid (GABA), encephalin, or beta endorphin which lead to eliminate anxiety, depression and stress neurotransmitters, resulting in calmness feeling. Method: This research is a case control study with quasi-experimental design. Total of 30 respondents who were breast cancer chemotherapy patients at Ibnu Sina Hospital of Makassar, divided into two groups. The first group received voice recording of the Murrotal Al-Quran for 30 minutes with the same Qori and surah (Al-Ikhlas, Al-Falaq and An-nas) while the other group were treated with 0,5 mg alprazolam tablets. Interviews and measurements of anxiety level were measured using the Hamilton Anxiety Rating Scale carried out before and 60 minutes after treatment in both groups. Purposive sampling technique were used to collect data and analysed with Wilcoxon test. Result: Significant anxiety levels improvements take place in both treatment groups (p<0.05), without any significant differences (p=0,13). Murrotal listening has the same effect as anti-anxiety drugs. The advantage of murrotal listening compared with medication are: easy administration method, no side effects and does not require a doctor's prescription, and get a spiritual reward. Conclusion: Murrotal listening has a good inpact in improving anxiety level of breast cancer patients undergoing chemotherapy.